2015
DOI: 10.3389/fnbeh.2015.00229
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study investigating changes in neural processing after mindfulness training in elite athletes

Abstract: The ability to pay close attention to the present moment can be a crucial factor for performing well in a competitive situation. Training mindfulness is one approach to potentially improve elite athletes’ ability to focus their attention on the present moment. However, virtually nothing is known about whether these types of interventions alter neural systems that are important for optimal performance. This pilot study examined whether an intervention aimed at improving mindfulness [Mindful Performance Enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 71 publications
1
33
0
3
Order By: Relevance
“…The inspiratory breathing load paradigm has been used to study aversive interoception in healthy and psychiatric populations (Berk et al 2015; Galli et al 2013; Haase et al 2015; Haase et al 2014; Paulus et al 2012; Stewart et al 2014). During fMRI scanning, participants wore a nose clip and were instructed to breathe through a hose that intermittently restricted breathing for 40-s periods via 40 cm H20/L/sec inspiratory loads (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inspiratory breathing load paradigm has been used to study aversive interoception in healthy and psychiatric populations (Berk et al 2015; Galli et al 2013; Haase et al 2015; Haase et al 2014; Paulus et al 2012; Stewart et al 2014). During fMRI scanning, participants wore a nose clip and were instructed to breathe through a hose that intermittently restricted breathing for 40-s periods via 40 cm H20/L/sec inspiratory loads (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The well-validated task has been shown to activate regions of the insula, PFC, striatum, and anterior cingulate (Berk et al 2015; Galli et al 2013; Paulus et al 2012; Stewart et al 2014). The majority of prior data from this paradigm suggest that less healthy or less resilient individuals tend to show reduced activation during anticipation and increased activation during breathing load (Berk et al 2015; Haase et al 2015; Haase et al 2016; Haase et al 2014; Paulus et al 2012; see Table S1 for summary). Unlike brief pain, taste, or food picture tasks previously used to study RAN (Cowdrey et al 2011; Oberndorfer et al 2013a; Strigo et al 2013), the breathing load paradigm uses prolonged, aversive stimulation to induce a negative interoceptive state while importantly avoiding the confounds of symptom-specific responses to food stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Such episodes can occur approximately 30% (Kane et al 2007) to nearly 50% (Killingsworth and Gilbert 2010) of waking hours and can result in decreased emotional well-being (Killingsworth and Gilbert 2010). Lapses in sustained attention could have particularly deleterious effects during athletic performance, which requires keeping performance goals online while maintaining situational and interoceptive awareness (Haase et al 2015). Thus, the margins of victory may be determined by one's success at maintaining sustained attention.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomised controlled trial of a mindfulness-based intervention delivered to employees, Davidson et al (2003) found a significant pre-post increase in relative leftsided hemispheric activationa pattern associated with wellbeingin the experimental group (while the intervention also appeared to positively affect immune function). More recently, Haase et al (2015) explored the impact of mindfulness training on neural processing in elite athletes, linking this to outcomes such as increased activation of the anterior cingulate cortex (a brain region implicated in executive attention). Such research is in its infancy, and is an exciting area for future studies to explore.…”
Section: Neurons and Neural Networkmentioning
confidence: 99%